2012
DOI: 10.1016/j.susc.2012.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative local structure determination of R,R-tartaric acid on Cu(110): Monotartrate and bitartrate phases

Abstract: The local adsorption site of the monotartrate and bitartrate species of R,R-tartaric acid deposited on Cu(110) have been determined by scanned-energy mode photoelectron diffraction (PhD). In the monotartrate phase the molecule is found to adsorb upright through the O atoms of the single deprotonated carboxylic acid (carboxylate) group, which are located in different off-atop sites with associated Cu-O bondlengths of 1.92±0.08Å and 1.93±0.06Å; the plane of the carboxylate group tilted is by 17±6° off the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In the (40,23) structure a close packed aggregate of monotartrate (the singly deprotonated form of TA) forms a full monolayer. A model with two anchorage points was suggested based on STM images [1] and on a recent quantitative structural model based on scanned-energy mode photoelectron diffraction experiments [31]. We determined the most stable R,R-TA conformer in the (40,23) phase by means of DFT calculations and modeled its configuration on Cu(110) to obtain an accurate description of the electronic properties of the system.…”
Section: Resultsmentioning
confidence: 99%
“…In the (40,23) structure a close packed aggregate of monotartrate (the singly deprotonated form of TA) forms a full monolayer. A model with two anchorage points was suggested based on STM images [1] and on a recent quantitative structural model based on scanned-energy mode photoelectron diffraction experiments [31]. We determined the most stable R,R-TA conformer in the (40,23) phase by means of DFT calculations and modeled its configuration on Cu(110) to obtain an accurate description of the electronic properties of the system.…”
Section: Resultsmentioning
confidence: 99%
“…The dissociative adsorption of formic acid, according to LEED, lifted the SCV reconstruction giving a LEED pattern indicative of a bulk-like termination. A recently published surface X-ray diffraction (SXRD) study by Arndt et al 23 has shown that the formate is bound to two surface Fe oct cations through its two carboxylate oxygens, O HCOO , which is consistent with how formate [24][25][26][27][28][29] and more broadly the carboxylate functional group, [30][31][32][33][34][35][36][37] bonds with most surfaces. Moreover, they were able to determine that the formate molecule preferentially binds to one of the two bidentate adsorption sites, the 'tet' adsorption site, with the formate carbon atoms coincident with the 1st subsurface Fe tet in the [110] crystallographic direction, shown in Fig.…”
Section: Introductionmentioning
confidence: 84%
“…Many interesting results have been obtained in studies on selfassembled monolayers (SAMs). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Recently, STM has been applied to study SAMs of glycine and alanine molecules on Cu(110), 12,13) Cu(111), [14][15][16][17][18] and Cu(001) [19][20][21] surfaces and has shown the importance of chirality in their self-organization mechanisms and in producing their characteristic electronic structures. Glycine and alanine are interesting molecules because of their specific characteristics regarding chirality.…”
Section: Introductionmentioning
confidence: 99%